Investment and growth in the time of climate change - Atanas Kolev; Armin-D. Riess; Georg Zachmann; Edward Calthrop (European Investment Bank (EIB), 2012)
Cognisant of the many facets of climate change, this report looks through the lens of economics, that is, the social science that measures the economic impact of climate change and the costs and benefits of trying to mitigate it and adapt to it. From an investment perspective, issues for study include the balance between investment in mitigating greenhouse-gas emissions and adaptation to climate change; the urgency and timing of investing in both; obstacles to investment; and policies to remove them and make investment profitable. From a growth perspective, issues of interest include the link between climate action and economic growth; the short-term and the long-term dimensions of this link; and the importance of innovation as an interface between climate action and economic growth. One of the key messages from this report is that there is unexploited scope for making Europe's climate action more efficient, growth-friendly, and in tune with fiscal constraints.
Keywords: 330